Higher quality nutrition care process documentation predicts nutrition diagnosis improvement in the Academy of Nutrition and Dietetics breastfeeding registry study - Gaubert, Allison; Long, Julie M.; Woodcock, Lindsay; Wright, Lauri; Colin, Casey; Hamadi, Hanadi; Papoutsakis, Constantina (Frontiers in Nutrition, 2025)
IntroductionRegistered dietitian nutritionists (RDNs) provide medical nutrition therapy (MNT) to improve public health outcomes, yet RDNs impact on breastfeeding outcomes remains underexplored. The Breastfeeding Registry Study addresses this gap by examining MNT provided to breastfeeding infants. This study describes Nutrition Care Process (NCP) documentation patterns, evaluates documentation quality, and reports nutrition diagnosis improvement, goal attainment, and outcomes predictors.MethodsThis prospective, observational study included documentation from breastfeeding infants (n = 92) from July 2020 to June 2024 using the Academy of Nutrition and Dietetics Health Informatics Infrastructure. The primary outcome was breastfeeding duration. Frequencies of documented NCP terminology, impactful care plans, and nutrition diagnosis improvement were assessed. Documentation quality was evaluated using the NCP Quality Evaluation and Standardization Tool (NCP-QUEST). Mixed-effects logistic regression was used to identify predictors of improved outcomes.ResultsDuration of any breastfeeding averaged 34.2 ± 7.5 (mean ± SD) days (n = 10), although documentation of this indicator was poor. The most frequent etiology was breastfeeding difficulty (18%). Common intervention categories were Food and/or Nutrient Delivery (46%) and Coordination of Nutrition Care (43%). At reassessment, 68% of diagnoses improved, with the highest rates for breastfeeding difficulty (55%), predicted breastfeeding difficulty (83%), inadequate vitamin D intake (83%), and underweight (83%). NCP-QUEST score (OR = 1.58, 95% CI [1.02, 2.45] p = 0.042) and frequency of registered dietitian visits (OR = 1.77, 95% CI [0.34, 0.9.33] p = 0.049) predicted diagnosis improvement.DiscussionHigher-quality documentation and more RDN visits were associated with improvements in breastfeeding infants' nutrition diagnoses. This is the first known study to describe comprehensive care plans delivered by RDNs that improved prevalent lactation-related nutrition problems and to propose standards for documenting breastfeeding care data in alignment with global breastfeeding standards.